ABC : Arte Brasileira Contemporânea - Pedrosa, Adriano; Duarte, Luisa (São Paulo : Cosac Naify, 2013)
Milhazes, Beatriz ; Gomes, Fernanda ; Ramos, Nuno ; Mano, Rubens ; Longo Bahia, Dora ; Leirner, Jac ; Modé, João ; Catunda, Leda ; Chaves, Marcos ; Basbaum, Ricardo ; Costi, Rochelle ; Muniz, Vik ; de Souza, Edgard ; Cassaro, Franklin ; Bento, José ; Vinci, Laura ; Trope, Paula ; Andrade, Rodrigo ; Rennó, Rosângela ; Ferro, Chelpa ; Rennó, Cristiano ; do Espírito Santo, Iran ; Macchi, Jorge ; Varejão, Adriana ; De Almeida, Caetano ; Dias & Riedweg ; Almeida, Efrain ; Neto, Ernesto ; Lopes, Jarbas ; Guimarães, Cao ; Gonzalez-Foerster, Dominique ; Rufino, José ; Aïnouz, Karim ; Koch, Lucia ; Bethônico, Mabe ; Cabelo ; Garaicoa, Carlos ; Ortega, Damián ; Rolla, Marco Paulo ; O Grivo ; Neuenschwander, Rivane ; Guimarães, Tamar ; Avaf-Assume Vivid Astrofocus ; Damasceno, José ; Cinto, Sandra ; Lemos Auad, Tonico ; da Cunha, Alexandre ; Dias Nunes, Valdirlei ; Marepe ; Restiffe, Mauro ; Verzutti, Erika ; Araujo, Juan ; Lima, Laura ; Lucas, Renata ; Peres, Fernando ; Galan, Marcius ; Zaccagnini, Carla ; E Lain, Detanico ; Dardot, Marilá ; Ianês, Mauricio ; de Medeiros, Virginia ; Packer, Amilcar ; Marcelle, Cinthia ; Zamora, Héctor ; Matheus, Rodrigo ; Costa, Adriano ; Bolsoni, Débora ; Sierra, Gabriel ; Robbio, Nicolás ; Ramo, Sara ; Mira Brander, Leya ; Nepomuceno, Maria ; Steegmann Mangrané, Daniel ; Motta, Pedro ; Lagomarsino, Runo ; Komatsu, André ; Cidade, Marcelo ; Blass, Tatiana ; Marcellvs L. ; Rocha Pitta, Matheus ; Rocha Pitta, Thiago ; de Andrade, Jonathan ; Cass, Rodrigo ; Craveiro, Theo ; Borges, Sofia ; Gilbert, Deyson
boek
Keywords: Brazilië